POST MERGER FINANCIAL PRODUCT DIVERSIFICATION (CASE STUDY OF INDONESIAN SHARIA BANK) - R. Agrosamdhyo (International Forum of Researchers and Lecturers, 2022)
The purpose of this research is to find out how product diversification is carried out by Bank Syariah Indonesia after the merger to attract customers. The research methodology used is descriptive qualitative research. The informants in this study were employees of the Denpasar Branch of Bank Syariah Indonesia using a purposive technique. As well as data collection in the form of interviews and documentation. This study describes the results of product diversification carried out by Bank Syariah Indonesia after the merger to attract customers, namely by launching BSI products that were launched which did not exist in previous banks, namely Imas and BSI smart agents. Verification conducted by Indonesian Islamic banks is more effective in increasing customer interest which is increasing every month and is also suitable for expanding market share.